Enhancing Service Quality of Islamic Savings Products: A Strategy to Improve Customer Interest in SAHARA BMT NU East Java - Rudi Ruskiyanto; Razali Razali; Ahmad Majdi Tsabit (Faculty of Sharia and Islamic Economic, Universtas Annuqayah, 2025)
This study explores the enhancement of service quality for Islamic savings products at BMT NU East Java, specifically focusing on the SAHARA (Savings for Hajj and Umrah Arrangements) product designed to facilitate religious pilgrimages. Using qualitative field research conducted from January to April 2024, the study examines current service quality dimensions and their impact on customer interest. Findings reveal that BMT NU East Java employs three primary service approaches: